Johannes Itten - Wagner, Christoph, 1964- (The Great masters of art, 2019)
When the State Bauhaus opened in Weimar in 1918, the Swiss artist and art theorist Johannes Itten (1888 - 1967) was one of the first teachers to be appointed by Walter Gropius. With his preliminary course, Itten had a considerable effect on the creative training in the Bauhaus; to this day his insights into the theory of colours set standards in art education and in the field of design. Enquiring mind and lecturer, painter and art teacher - Johannes Itten was a very thoughtful artist personality which was reflected in numerous theoretical texts and artworks covering a wide range of styles. Constantly in dialogue with students and colleagues as well as in a study of other cultures and artistic ideas, Itten created works in which he examined colours, their aura, contrasts and forms. Inspired by Adolf Hoelzel, his teacher at the Stuttgart Academy, Itten developed, amongst other things, the famous doctrine of colour types whose significance extends far beyond the realms of art into everyday culture. The acknowledged Itten expert Christoph Wagner introduces the artist with his complex and symbolic work and traces an arc from the revolutionary Bauhaus teacher and founder of various art schools to the art theorist of the theory of colours.